Fenomena Frugal life yang Berlebihan Pada Penerapan Filsafat Materialisme Menurut Matius 6:21 - Laoli, Septiniar; Snae, Ninci; Waruwu, Nistari; Zega, Septria; Samemek, Kristina Elmawati (Institut Agama Kristen Negeri Tarutung, 2024)
The phenomenon of excessive frugal life is common in today's modern society. This raises interesting philosophical questions regarding the relationship between material wealth and spiritual value. This article aims to analyze this phenomenon through the perspective of the philosophy of materialism, specifically regarding the teachings of Matthew 6:21. The philosophy of materialism emphasizes the physical or material aspects of human life, including wealth, possessions, and the satisfaction of material needs. Referring to the teachings of Matthew 6:21, this article will also discuss the relationship between wealth and heart in the context of excessive frugality. By combining the philosophy of materialism and the theological aspects contained in the teachings of Matthew 6:21, this article seeks to provide insights into how excessive frugality affects views on wealth, happiness, and life values. We hope that this research can spark new discussions on how we view and respond to social phenomena in a world that is increasingly focused on the material aspects of everyday life.